2019
DOI: 10.3389/fonc.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Diagnostic Accuracy of Contrast-Enhanced Ultrasound and Shear Wave Elastography in Differentiating Benign and Malignant Lesions: A Network Meta-Analysis

Abstract: Background: We performed a network meta-analysis to compare the diagnostic accuracy of contrast-enhanced ultrasound (CEUS) and shear wave elastography (SWE) in differentiating benign and malignant lesions in different body sites.Methods: A computerized literature search of Medline, Embase, SCOPUS, and Web of Science was performed using relevant keywords. Following data extraction, we calculated sensitivity, specificity, positive likelihood ratio (LR), negative LR, and diagnostic odds ratio (DOR) for CEUS, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 116 publications
2
19
0
Order By: Relevance
“…This approach has high sensitivities ranging from 95 to 97%, but low specificities ranging from 55 to 68%, in the differentiation between benign and malignant breast masses ( 33 ). Quantitative SWE parameters have been reported to be able to classify breast lesions with a specificity of 86% and a sensitivity of 84% ( 14 ). Among the quantitative SWE parameters, E max , E mean , E ratio , and E SD are the most commonly used indexes for the differential diagnosis ( 7 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has high sensitivities ranging from 95 to 97%, but low specificities ranging from 55 to 68%, in the differentiation between benign and malignant breast masses ( 33 ). Quantitative SWE parameters have been reported to be able to classify breast lesions with a specificity of 86% and a sensitivity of 84% ( 14 ). Among the quantitative SWE parameters, E max , E mean , E ratio , and E SD are the most commonly used indexes for the differential diagnosis ( 7 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that quantitative SWE parameters are reproducible for assessing elastographic features of breast masses and can improve the diagnostic specificity of B-mode US without loss of sensitivity ( 5 , 7 , 13 ). However, the specificity remains limited up to 86% when the quantitative SWE parameters were used ( 14 ). Therefore, a method to improve the diagnostic performance, especially to further improve the specificity of B-mode US or SWE, for the classification of breast lesions is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Since the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) released the Guidelines and recommendations for the hepatic use of contrast-enhanced ultrasound (CEUS), CEUS has been used for non-hepatic applications because of its advantages in visualizing the microcirculation and the dynamic enhancing process of tumors (5,9,10). Previous studies have shown the good performance of CEUS in differentiating benign and malignant thyroid nodules and screening appropriate nodules for FNA, as an effective supplement technique of conventional US (11)(12)(13). And the diagnostic accuracy of thyroid nodules can be increased by combining conventional US and CEUS (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Since SWE was brought in clinical practice a number of studies have been conducted on its reliability and compared it with the conventional modes of imaging including ultrasound and mammograms. In addition to individual studies a number of meta-analysis has also been done [4][5][6]. Invariably all the studies showed superiority of SWE over ultrasound and mammograms alone in particular BIRAD 3 and 4 cases.…”
Section: Reliability Of Swe As Imaging Modality In Breast 51 Swe Difmentioning
confidence: 99%